A propósito de los conceptos de velocidad y rapidez: una propuesta de formalización en la enseñanza de la física de estos conceptos desde la perspectiva Galileana - Osorio Quintero, Rusbley Yadit; Aguilar Mosquera, Yirsen (Revista Científica, 2011)
﻿﻿In the analysis made in educational research on science teaching are evident difficultiesstudents have in the ways of conceptualizing the physical phenomena of the speed andquickness, in the explanations given by the students of the movement is not set differencebetween these concepts. This is problematic when dealing with situations involvinguniform circular motion, which is important to distinguish between these concepts.With the intention to build conceptual alternative routes to teaching movement is a historical analysis of how epistemological Galileo set and introduces the concepts of speedand quickness, as set out in his book Mathematical Considerations and Demonstrations(1976) on Two New Science. This analysis shows how Galileo makes a distinction betweenthe speed and quickness, regarded as a magnitude speed-intensive and extended thespeed and magnitude. It also examines how the use of geometry in the organization ofthe phenomenon of movement that allows Galileo to shape this kind of phenomena, anaspect which constitutes a fruitful way to signify the relationship between physics andmathematics.